Reconstruction of the Meaning of Ṣhadr, Qalb, and Fu’ād in the Qur’an and Its Implications for Arabic Language Pedagogy - Olifia, Wafa; Syafi’i, Ahmad Hilwani; Izomi, M. Syahrul; Mukhlishin, Mukhlishin (Journal of Educational Sciences, 2026)
Arabic language learning often treats the Qur’anic terms ṣadr, qalb, and fu’ād as synonymous, which obscures their distinct semantic meanings and limits students’ conceptual understanding. This study aims to reconstruct the semantic differences among these three Qur’anic terms and examine their implications for Arabic language pedagogy. This research employs a descriptive qualitative approach based on Qur’anic semantic analysis using Toshihiko Izutsu’s semantic field theory. Data were analyzed through textual examination of Qur’anic verses containing the three terms and supported by semi-structured interviews with Arabic teachers and students to explore their understanding of these concepts in learning contexts. The findings show that ṣadr refers to the domain of inner openness and receptivity, qalb represents the dynamic center of cognitive and moral transformation, and fu’ād denotes a deeper level of emotional and reflective awareness. Field data also indicate that Arabic instruction tends to emphasize structural aspects of language and rarely incorporates semantic distinctions derived from Qur’anic concepts. This study concludes that integrating Qur’anic semantic analysis into Arabic pedagogy can enrich vocabulary comprehension and promote more meaningful and interpretive language learning.